Exposure to particulate matter 2.5 and cigarette smoke induces the synthesis of lipid droplets by glycerol kinase 5. (18th January 2021) - Yan, Mengnan; Wu, Yuanyuan; Peng, Wenjun; Fu, Cuiping; Giunta, Sergio; Chang, Meijia; Zhang, Ge; Dou, Maosen; Xia, Shijin; Li, Huayin; Zhou, Jian; Shen, Yao
Abstract: Particulate matter (PM2.5) and cigarette smoke exposure are leading factors contributing to various diseases, especially respiratory diseases. The purpose of this research was to study the effects of PM2.5 and cigarette smoke on glycerol kinase 5 (GK5) expression and the possible mechanisms by which GK5 participates in lipid droplet (LD) synthesis in alveolar epithelial A549 cells. Real‐time polymerase chain reaction (RT‐PCR) and western blotting have been used for the detection of messenger RNA (mRNA) and protein expression respectively. GK5 overexpressing cells were established by lentivirus transfection, whereby lentiviral vectors deliver the gene into chromosomes, allowing stable expression. Affymetrix microarray analysis, a widely used tool for measuring genome‐wide gene expression, has been used to explore differential gene expression profiles. A549 cells stimulated with PM2.5 and cigarette smoke extract (CSE) showed elevated GK5 expression in a dose‐dependent manner. Transmission electron microscopy and oil red O staining were used to observe LDs in cells. Further, GK5 overexpressing cells showed increased LDs and upregulation of genes and proteins related to lipogenesis and lipid transportation. Affymetrix microarray analysis revealed that GK5 overexpression resulted in the differential expression of more than 109 genes, which were mainly involved in the regulation of cell death, cell survival, cellular movement and migration, and those involved in cellular growth and proliferation pathways. Overall, this study demonstrates that GK5 is upregulated during PM2.5 and cigarette smoke exposure and induces LD synthesis. Abstract : GK5 is upregulated during PM2.5 and cigarette smoke exposure and induces lipid droplet synthesis.